Obsessive-compulsive personality disorder: a challenging case treated with a psychopharmacological approach (Bangladesh Journal of Psychiatry, 2022)
Obsessive-compulsive personality disorder is a subcategory of personality disorder, though prevalent is a less researched condition. Psychotherapy is the mainstay of treatment but provided data on its effectiveness are scarce. The case presented involves an unhappy 26-year[1]old lady preoccupied with perfectionism, inflexibility, reluctance to collaborate with others with significant interpersonal distress, and functional impairment. In addition to pharmacological treatment, psychological interventions including cognitive behaviour therapy, problem-solving counselling, and coping strategies were exercised on the ground of a trusting therapeutic alliance. Considerable improvement was noticed.Bang J Psychiatry 2022;36(1):18-20